Estimating the Effects of Non-discriminatory Trade Policies within Structural Gravity Models - Benedikt Heid; Mario Larch; Yoto V. Yotov (Center for Economic Studies and ifo Institute (CESifo), 2017)
We propose a simple method to identify the effects of unilateral and non-discriminatory trade policies on bilateral trade within a theoretically-consistent empirical gravity model. Specifi-cally, we argue that structural gravity estimations should be performed with data that include not only international trade flows but also intra-national trade flows. The use of intra-national sales allows identification of the effects of non-discriminatory trade policies on the importer side (e.g. most favored nation tariffs) and on the exporter side (e.g. export subsidies), even in the presence of exporter and importer fixed effects. An important byproduct of our approach is that it can be used to recover estimates of the export-supply elasticity and of the import-demand elasticity. We demonstrate the effectiveness of our techniques in the case of MFN tariffs and “Time to Export” as representative determinants of trade on the importer and on the exporter side, respectively. Our methods can be extended to quantify the impact on trade of any country-specific characteristics as well as any non-trade policies.
Keywords: F10; F13; F14; F47; 330; gravity model; non-discriminatory trade policies; tariffs; subsidies; time to export; trade elasticity of substitution